2007
DOI: 10.1111/j.1095-8649.2007.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the gastrointestinal tract and selected digestive enzymes in cobia Rachycentron canadum (L.)

Abstract: The ontogeny of the digestive system of cobia Rachycentron canadum from hatching to 22 days post-hatch (dph) (20Á1 mm standard length) was examined with light microscopy. The activities of selected pancreatic enzymes were also determined during this period in order to optimize current rearing methods for this species. At hatching (3Á6 mm), the digestive tract consisted of a relatively undifferentiated, straight tube positioned dorsally to the yolk sac. The major morphological changes in the digestive tract pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 47 publications
(66 reference statements)
4
45
1
3
Order By: Relevance
“…In the earlier case, CCK levels between 0.5 -1.0 fmol larva -1 found for larval cod of comparable age (to 17 dph in Kortner et al, 2011b) in the present study might be the threshold for the regulatory role of CCK in larval cod. In general, the developmental pattern of different digestive enzymes has been described in several species, including California halibut (Paralichthys californicus) (AlvarezGonzález et al, 2005), sea bass (Cahu and Zambonino Infante, 1994), cobia (Rachycentron canadum) (Faulk et al, 2007), red drum (Sciaenops ocellatus) (Lazo et al, 2000a) and Atlantic cod (Wold et al, 2007) and has been found to be speciesspecific. It has been proposed, that digestive enzyme activities in early stages of marine fish larvae are under transcriptional control, but can be triggered by the nutritional composition of the diet (Zambonino Infante and Cahu, 2001).…”
Section: Ontogenymentioning
confidence: 99%
“…In the earlier case, CCK levels between 0.5 -1.0 fmol larva -1 found for larval cod of comparable age (to 17 dph in Kortner et al, 2011b) in the present study might be the threshold for the regulatory role of CCK in larval cod. In general, the developmental pattern of different digestive enzymes has been described in several species, including California halibut (Paralichthys californicus) (AlvarezGonzález et al, 2005), sea bass (Cahu and Zambonino Infante, 1994), cobia (Rachycentron canadum) (Faulk et al, 2007), red drum (Sciaenops ocellatus) (Lazo et al, 2000a) and Atlantic cod (Wold et al, 2007) and has been found to be speciesspecific. It has been proposed, that digestive enzyme activities in early stages of marine fish larvae are under transcriptional control, but can be triggered by the nutritional composition of the diet (Zambonino Infante and Cahu, 2001).…”
Section: Ontogenymentioning
confidence: 99%
“…Studies dealing with organs and tissue development during the early life history of cobia are scarce, and mainly focus on the digestive tract development (Faulk et al 2007, Salze et al 2011. The aim of this study is to describe the thyroid follicle development in cobia larvae and juvenile.…”
mentioning
confidence: 99%
“…and Chironomids+M.D. negatively affected the digestion and absorption capabilities due to possibly inadequate enzyme secretion (Faulk et al, 2007). Then, the protease activity was on the rise in an orderly manner after DAH 25.…”
Section: Discussionmentioning
confidence: 95%